2015
DOI: 10.1111/geb.12338
|View full text |Cite
|
Sign up to set email alerts
|

Global‐scale mapping of changes in ecosystem functioning from earth observation‐based trends in total and recurrent vegetation

Abstract: Aim To evaluate trend analysis of earth observation (EO) dense time series as a new way of describing and mapping changes in ecosystem functioning at regional to global scales. Spatio-temporal patterns of change covering 1982-2011 are discussed in the context of changes in land use and land cover (LULCC). Location Global.Methods This study takes advantage of the different phenological cycles of recurrent vegetation (herbaceous vegetation) and persistent vegetation (woody/shrub cover) in combining trend analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…They also employed the TIMESAT approach, but with different parameter settings as compared to this study, indicating the robustness of the method for phenology retrieval and consequently the results obtained in this study. Moreover, the calculated trends in GSI ( Figure 2D) are in agreement with the result from Fensholt et al [53], although their study period (1982-2011) was two years shorter than this study.…”
Section: Trends In Vegetation Phenology and Growing Season Integralsupporting
confidence: 92%
See 1 more Smart Citation
“…They also employed the TIMESAT approach, but with different parameter settings as compared to this study, indicating the robustness of the method for phenology retrieval and consequently the results obtained in this study. Moreover, the calculated trends in GSI ( Figure 2D) are in agreement with the result from Fensholt et al [53], although their study period (1982-2011) was two years shorter than this study.…”
Section: Trends In Vegetation Phenology and Growing Season Integralsupporting
confidence: 92%
“…This is further supported by Xia [69] et al who revealed that the inter-biome variations in annual GPP can be better explained by the variations in seasonal maximal photosynthetic capacity than LOS. In addition to the impact from ongoing global warming and natural climate variability, the relationship between vegetation phenology and productivity could also be affected by changes in both/either vegetation metrics induced by anthropogenic land use/cover changes (e.g., deforestation/afforestation, land clearing, irrigation and fertilization, and changes in land management practices) [53,60,[74][75][76]. Whereas, it could be assumed that changes in land management may also cause divergence between LOS and GSI (e.g., a change from one crop-type to another with different LOS/GSI characteristics), it is noteworthy that both converging trends and pixels with significant positive correlations between LOS and GSI are more pronounced for mixed forest than for the three natural forest biomes, which is also the case for croplands as compared to the three natural non-forest biomes ( Figures 4A and 6B).…”
Section: Converging/diverging Trends and Correlations Between Los Andmentioning
confidence: 99%
“…Global scale studies demonstrated the applicability of the NDVI3g, the longest available remote sensing dataset [25], in trend detection of the phenological cycle and sensitivity studies (e.g., [34,[36][37][38][40][41][42][83][84][85]). Nevertheless, evaluation of NDVI3g for regional application is necessary due to known issues and uncertainties [32][33][34][35].…”
Section: Modis Ndvi As Reference Dataset For Ndvi3g Evaluationmentioning
confidence: 99%
“…It is an important method in vegetation change trend analysis to carry out a regression analysis of time-varying variables and to predict their trends [17,[50][51][52][53]. The slope of the equation developed using linear least square fitting of long time NDVI series shows NDVI trends over several years.…”
Section: Trend Analysis Of Vegetation Dynamicsmentioning
confidence: 99%